2007
DOI: 10.1016/j.ijpsycho.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Affective visual event-related potentials: Arousal, valence, and repetition effects for normal and distorted pictures

Abstract: Event-related potentials (ERPs) were used to assess arousal (low, high), valence (negative, positive), and stimulus repetition effects for normal and distorted images from the International Affective Pictures System (IAPS). Distorted stimuli were constructed by dividing each image into 108 one cm squares and rearranging the segments randomly to produce a "scrambled" picture. Event-related potentials (ERPs) were elicited by presenting the normal and scrambled images as target stimuli, with a repeated visual pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 57 publications
6
53
0
2
Order By: Relevance
“…The grandaverage EEG of epochs time-locked to stimulus onset revealed a positive waveform in the 200-to 400-ms window. This waveform increased in magnitude from the frontal to the parietal electrodes and was compatible with previous findings for the P300 (Polich & Kok, 1995), a wave previously described that can be modulated by emotion (CarretiĂ©, Iglesias, & GarcĂ­a, 1997;CarretiĂ©, Iglesias, GarcĂ­a, & Ballesteros, 1997;Olofsson et al, 2008;Olofsson & Polich, 2007;Rozenkrants, Olofsson, & Polich, 2008;Schupp, Cuthbert, Bradley, Birbaumer, & Lang, 1997). Figure 5 depicts the grand averages obtained at the frontal, central, and parietal midline electrodes (Fz, Cz, and Pz).…”
Section: Resultssupporting
confidence: 88%
“…The grandaverage EEG of epochs time-locked to stimulus onset revealed a positive waveform in the 200-to 400-ms window. This waveform increased in magnitude from the frontal to the parietal electrodes and was compatible with previous findings for the P300 (Polich & Kok, 1995), a wave previously described that can be modulated by emotion (CarretiĂ©, Iglesias, & GarcĂ­a, 1997;CarretiĂ©, Iglesias, GarcĂ­a, & Ballesteros, 1997;Olofsson et al, 2008;Olofsson & Polich, 2007;Rozenkrants, Olofsson, & Polich, 2008;Schupp, Cuthbert, Bradley, Birbaumer, & Lang, 1997). Figure 5 depicts the grand averages obtained at the frontal, central, and parietal midline electrodes (Fz, Cz, and Pz).…”
Section: Resultssupporting
confidence: 88%
“…Focused on emotional arousal, some studies have demonstrated that highly emotionally arousing stimuli elicit more pronounced P300 waves than low emotionally arousing stimuli, even when these stimuli are presented without awareness (Feng, Wang, Liu, Zhu, Dai, Mai, & Luo, 2012;Rozenkrants, Olofsson, & Polich, 2008). These previous findings are in accord with the current study, confirming that emotional arousal increases P300 responses to probes in the CIT, regardless of conscious awareness.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it remains unclear whether crime-related stimuli are also automatically recognized in the CIT, like selfname stimuli. Previous studies have demonstrated that highly emotionally arousing stimuli elicit more pronounced P300 waves than less emotionally arousing stimuli, even when these stimuli are presented without conscious recognition (Feng, Wang, Liu, Zhu, Dai, Mai, & Luo, 2012;Rozenkrants, Olofsson, & Polich, 2008). In line with these studies, a crime-related probe might also be processed via the bottom-up route if it is perceived unconsciously.…”
Section: Introductionsupporting
confidence: 61%
“…Previous research showed that VEPs are sensitive to both physical and semantic features of visual stimuli (Keil et al, 2002;Rozenkrants et al, 2008).…”
Section: "I'm Not Afraid Of Death; I Just Don't Want To Be There Whenmentioning
confidence: 99%